(untitled) (ACTA MEDICA PERUANA, 2022)
Drug reaction with eosinophilia and systemic symptoms (DRESS) is a very rare syndrome characterized by skin rash, eosinophilia and systemic compromise. This was initially described in association with antiseizures drugs, but later it was described in association with other drugs. Among antiseizure drugs, it has been described association with aromatic drugs as phenytoin, carbamazepine, phenobarbital, oxcarbazepine and lamotrigine; and non-aromatic antiseizure drugs as gabapentin, zonisamide, valproate, rufinamide and rarely to levetiracetam. The severity of the syndrome is related to the time of exposure to the drug, so early detection is of vital importance. We describe the first case in our country, of a patient with DRESS induced by levetiracetam, and we review the infrequent scientific reports of DRESS in patients exposed to levetiracetam.